Neuroendocrine immune system in familial Mediterranean fever - Topaloğlu, Rezan; Bilginer, Yelda; Alikaşifoğlu, Ayfer; Ozaltin, Fatih; Beşbaş, Nesrin; Ozen, Seza; Bakkaloğlu, Ayşin (The Turkish Journal of Pediatrics, 2010)
Familial Mediterranean fever (FMF) is an autoinflammatory disorder and is characterized by self-limited attacks of inflammation. Although mutations in the gene coding for pyrin are responsible for the inflammation seen in attacks, the question of whether the failure to mount an appropriate cortisol response to inflammation has any additive effects allowed us to plan this study. The aim was to determine the interactions between the neuroendocrine and immune system in patients with FMF and investigate the role of the neuroendocrine system in the acute inflammation process. Demographic characteristics, disease activity, mutation analysis, and duration of the disease were defined in 15 FMF patients (7 female, 8 male; mean age +/- SD: 9.1 +/- 4.2 years). The diagnosis was based on Tel-Hashomer criteria. Ten healthy volunteers and 21 active juvenile idiopathic arthritis (JIA) patients formed the control groups. Furthermore, 10 of these 15 patients with FMF were also studied during the attack-free period. Erythrocyte sedimentation rate (ESR) C-reactive protein (CRP), fibrinogen, adrenocorticotropic hormone (ACTH), cortisol, insulin-like growth factor-1 (IGF)-1, IGF binding protein (BP)-3, urinary cortisol levels, interleukin (IL)-1beta, IL-6, and tumor necrosis factor (TNF)-a were evaluated in FMF patients with attack and during the attack-free period. Although the median levels of ACTH (12.7 pg/ml) and cortisol (12 ug/dl) at 08:00 a.m. were lower in FMF patients during attack than in the attack-free period, these differences did not reach statistical significance. On the other hand, the median levels of ACTH were significantly lower during attack than in the healthy control group (p < 0.05). Median levels of IGF-1 (118.5 ng/ml) were significantly lower during FMF attack than in the attack-free period (p < 0.05). There was a negative correlation between IGF-1 and CRP (r = -0.47). The median level of IL-6 was 18.1 pg/dl during FMF attack and was significantly higher than in the attack-free period and in the healthy control group (p < 0.05). There was a negative correlation between cortisol level at 08:00 am and IL-6 (r = -0.45). When we compared JIA with FMF patients during attack, inappropriately low secretion of adrenal cortisol and ACTH and low urine cortisol levels were more pronounced in JIA than FMF Although it is more prominent in chronic inflammation, the neuroendocrine immune system seems to be impaired in relation to acute inflammation in FMF.